Strategi Manajemen Syariah Dalam Menghadapi Krisis Ekonomi - Rahma Fahmadina Lubis; Chuzaimah Batubara (Madani: Jurnal Ilmiah Multidisiplin, 2023)
An economic crisis is a serious challenge that can affect the economic stability of a country. Shariah management strategies It has proven to be an effective and sustainable approach to dealing with the economic crisis. The purpose of this study is to analyze the Shariah management process that can be used to address it.Â  economic crises. This study describes the fundamental characteristics of the Islamic economic system, including principles such as fairness, sustainability, transparency, and compliance with Sharia law. In situations of economic crisis, the Islamic Management Strategy builds on these principles to promote long-term economic stability.